Effect of Fe-doping on the structural, microstructural, optical, and ferroeletric properties of Pb1/2Sr1/2Ti1-xFexO3 oxide prepared by spin coating technique - Pontes, F. M. [UNESP]; Pontes, D. S. L.; Chiquito, A. J.; Pereira-da-Silva, Marcelo A.; Longo, E. [UNESP] (Elsevier B.V., 2015)
The influence of Fe content on the structural, microstructural, dielectric, ferroelectric and optical properties was investigated in Pb1/2Sr1/2Ti1-xFexO3 films deposited on Si/SiO2/Ti/Pt and quartz substrates. X-ray diffraction showed that all films presented polycrystalline and single perovskite phases and the change of lattice parameters caused by increasing Fe-doping content replacing Ti4+ ions is very small to be detected by X-ray diffraction technique. Micro-Raman analysis showed the tetragonal nature for both undoped-PSTF and cloped-PSTF (1%Fe) films, while both cloped-PSTF (5%Fe) and PSIT-10 (10%Fe) films presented a pseudocubic structure. It was noticed that all films exhibited a homogeneous microstructure, compact and crack-free. The remnant polarization in the Fe-doped PSTF films was weaker than that for undoped-PSTF films which was attributed to structural changes and smaller grain size. The increasing of Fe content leads to a red shifted band gap relative to undoped PSTF films due localized levels within the forbidden band of PSTF. (C) 2014 Elsevier BM. All rights reserved.
Keywords: Thin films; Ferroelectric properties; Optical properties; AFM; Perovskite